IL-33 Priming Enhances Peritoneal Macrophage Activity in Response to Candida albicans - Tran, Vuvi G. (The Korean Association of Immunologists, 2014)
IL-33 is a member of the IL-1 cytokine family and plays a role in the host defense against bacteria, viruses, and fungi. In this study, we investigated the function of IL-33 and its receptor in in vitro macrophage responses to Candida albicans. Our results demonstrate that pre-sensitization of isolated peritoneal macrophages with IL-33 enhanced their pro-inflammatory cytokine production and phagocytic activity in response to C. albicans. These macrophage activities were entirely dependent on the ST2-MyD88 signaling pathway. In addition, pre-sensitization with IL-33 also increased ROS production and the subsequent killing ability of macrophages following C. albicans challenge. These results indicate that IL-33 may increase anti-fungal activity against Candida through macrophage-mediated resistance mechanisms.